Revision of the genus Ariptyelus Matsumura (Hemiptera: Cercopoidea: Aphrophoridae) - Shih, Hsien-Tzung; Yang, Jeng-Tze (Zootaxa, 2007)
The genus Ariptyelus Matsumura, comprising 3 species, is reviewed. Two species, A. arisanus (Matsumura, 1942) and A. auropilosus (Matsumura, 1907) are redescribed. Ariptyelus arisanus is recorded only from Taiwan. A. auropilosus, previously known from Taiwan and China (Xizang, Sichuan, Yunnan, and Fujian) is newly recorded from Philippines, Indonesia, and Hainan, and Lutao and Orchid Islands. One new species from India and Nepal, A. subauropilosus sp. nov., is described. The diagnostic characters of the genera Ariptyelus and Peuceptyelus and the characters distinguishing the 3 species of Ariptyelus are presented.